Porous Nanofiber Membrane: Rational Platform for Highly Sensitive Thermochromic Sensor. (7th March 2022) - Kim, Dong‐Ha; Bae, Jaehyeong; Lee, Jiyoung; Ahn, Jaewan; Hwang, Won‐Tae; Ko, Jaehyun; Kim, Il‐Doo
Abstract: Thermochromic sensors provide an intuitive and real‐time solution for monitoring the local temperature with naked eyes. Conventional thermochromic sensors often utilize either solution‐type or dense film‐type platforms, which are suboptimal morphologies for exposing a large number of dye molecules to the surface, leading to low sensitivity and sluggish responding speeds. Herein, this article introduces rational synthetic routes to fabricate highly sensitive nanofiber (NF) sensor membranes loaded with thermochromic dyes (C3 H6 N6 ·CH2 O) x ‐loaded nanofibers (NFs) sensor membranes by alignment‐controllable electrospinning techniques ( x – y perpendicular and rotary). The NF‐based porous sensor membranes exhibit two‐ to fivefold improved thermochromic sensitivity (ΔRGB) compared to those of dense film‐type sensors at 31.6–42.7 °C. This is attributed to the uniform distribution of dyes throughout the porous NF structure (≈95.7%), which exhibits excellent light transmittance that is 10–30‐fold higher than that of film‐type sensors. Based on the available shape‐conforming synthetic strategies, this article further demonstrates wearable thermochromic sensors in the forms of mask‐, patch‐, and bracelet‐type devices, which can accurately monitor body temperature in real time. Abstract : Highly sensitive thermochromic sensors are developed using nanofiber (NF) membranes with tunable alignments of the fibers via fine‐tuned electric field during the electrospinning process. The porous NF membrane‐based sensors show five‐fold enhanced thermochromic sensing performance compared with dense film‐type sensors. The NF sensor membranes can be further integrated with masks, patches, and bracelets for wearable applications.